(untitled) (Management and Connections Journal, 2015)
The purpose of this paper is to analyze the marketing strategy of global and local energy drink brands in the Brazilian market. The author utilizes marketing strategy theories and competition analysis theories to support his arguments about the impact of these brands in Brazil. This paper is characterized as an exploratory study that provides a holistic framework to important strategic decisions that managers have to make. The results show that Brazil as a less developed economy tends to associate global brands as having a high quality than the local ones, so local brands are strategy adapting their products to being more similar with the well-known global brands.